ACCESS - IoT enabled smart lock - Harshith Gadupu; Osa Mokharji; Raunak Kankaria; Shrey Kumar; Kayalvizhi Jayavel (Institute of Advanced Engineering and Science, 2021)
ACCESS is a centrally controlled extensible security system - a system for enhancing accessibility and security methods. Security is an important matter of concern and everyone wants things easy and fast with the advancement of technology. Many IoT engineers are inclined towards home automation today. An area of recent interest is the automation of lock and key systems of homes and workplaces. This paper comprises mechanisms to view visitors of households, machinery, or any appliance that may be remotely controlled through a mobile application. Owners or supervisors can keep a watch on the guests and choose whom they want to grant entry to. This is conducted by providing the guests with temporary access permission for a validity period of the owner’s choice. They can also simultaneously monitor the activities of the guests.